PENGEMBANGAN MEDIA PEMBELAJARAN POP-UP BOOK DIGITAL PADA MATERI PERSATUAN DAN KESATUAN DI WILAYAH KABUPATEN ATAU KOTA SISWA KELAS V MIN 1 LANGSA - Mirna; Ayudia, Inge; Kumala Sari, Cut (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the limited use of digital learning media in the classroom. During the learning process, instruction was still predominantly conducted using textbooks and whiteboards, causing students to be more passive and experience difficulties in understanding abstract concepts. This study aimed to develop a digital pop-up book learning media and to determine its feasibility and practicality. The research employed the Research and Development (R&D) method using the ADDIE development model, which consists of five stages: (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. The research subjects consisted of 31 fifth-grade students of MIN 1 Langsa, one teacher as the learning practitioner, and three expert validators. Data were collected through observation, interviews, questionnaires, and documentation, while the data were analyzed using descriptive quantitative and qualitative analysis. The results showed that the developed digital pop-up book learning media achieved a very high level of feasibility based on expert validation, with a score of 96% from the material expert (very feasible), 98% from the language expert (very feasible), and 100% from the media expert at the final validation stage (very feasible). The learning practitioner's assessment obtained a score of 100%, indicating that the media was very practical. Therefore, the Digital Pop-Up Book Learning Media on the topic of Unity and Cohesion within Regency and City Areas was declared highly feasible and highly practical to be used as a supporting learning media for Pancasila Education in Grade V at MIN 1 Langsa.